De Berberse identiteit en het nieuwe meerpartijenstelsel in Algerije - Beke, Dirk (Afrika Focus, 1993)
The article first argues that the present population of Algeria can be designed as Arabo-Berber and Berber. The original inhabitants, collectively identified by most historians as Berbers, formed no physical ethnic unity, but they had a common Berber language and culture. The Islamisation of the population of North Africa proceeded faster and became almost general, this in contrast to the slower and more limited Arabisation. The physical-ethnic process of Arabisation by settlement and fusion was altogether restrained. The Arabisaiton was essentially a cultural process (language, popular culture, customs, politics, science, arts). About one fourth of the present Algerians resisted to (entire) Arabisation. They are living in, or originated from mountain or desert regions (Kabyles, Shawiya, Mozabites, Touareg). Since independence the official policy of Arabisation, against the strong influence of the French language, referred exclusively to Arabic character of the nation. All expressions of the Berber identity, culture and language were oppressed.Since 1980, a growing cultural revival, mainly among the Kabyles, reacted to this policy. The movement was rather cultural than political. The Berber speaking Algerians seem involved into many other regional and national alliances. With the introduction of the multi-partyism, in 1989, two ’Berber’ political parties became active: the FFS (Front des Forces socialistes) and the RCD (Rassemblement pour la Culture et la Démocratie). Both parties claim to be national parties and insist on defending, besides the recognition of the Berber identity and culture, general political options (socialism, democracy etc.). Electoral results, however, show that their support comes essentially from different factions of the Berber speaking population. It is obvious that the Berber ethnicity is used to gain electoral backing. Besides, today the two ’Berber’ parties represent the strongest opposition to the Islamic (= Arabic) fundamentalist party, the FIS (Front islamique de Salut), because of their resistance to social, cultural and political intolerance. Secessionist ideas based on Berber ethnicity live only among a small — but well-organised — minority. At the end of 1992, the Berber ethnicity is in Algeria primarily an element of cultural and regional recognition and only secondary an element of political coherence. Finally, Berber ethnicity has also invalidated the official political myth of the homogeneous Algerian Arabic ethnicity. KEY WORDS: Algeria, Arabs, Berbers, ethnicity, Islam, political parties